LATE BLIGHT RESISTANCE OF HYBRIDS OBTAINED IN CROSSES OF SOLANUM TUBEROSUM L. WITH THE BOLIVIAN DIPLOID POTATO SPECIES - N. M. Zoteyeva; Yu. I. Karabitsina (Труды по прикладной ботанике, генетике и селекции)
This paper presents the data of evaluation of late blight resistance in hybrids derived from crosses of Solanum tuberosum L. with the diploid Bolivian potato species S. berthaultii Hawk. and S. ruiz-ceballosii Card. selected previously for their resistance. In field and laboratory evaluation large share of resistant phenotypes was found. Both hybrids produced tubers in the field under long daylight conditions. S. berthaultii possesses a triploid number of chromosomes (2n = 36) and is completely sterile. Pollen grains of S. ruiz-ceballosii hybrid are partially fertile.